EFEK FORTIFIKASI VITAMIN B12 TERHADAP KADAR VITAMIN B12 SERUM DAN HOMOSISTEIN SERUM PADA VEGETARIAN - Susianto Susianto (Lembaga Penelitian Sekolah Tinggi Ilmu Kesehatan Kuningan, 2020)
Introduction: Vegetarians consume plant-based foods with or without eggs and milk. Vegetarians are at risk of vitamin B12 deficiency, as natural sources of vitamin B12 are limited to animal-based foods. Vitamin B12 deficiency can lead to megaloblastic anemia, nerve damage and increase homocysteine level. Higher homocysteine level can increase the risk of coronary heart disease and stroke. The objective of this study was to investigate the effect of vitamin B12 fortification on the level of serum vitamin B12 and homocysteine in vegetarian. Method: The research design was an experimental study, community trial. The samples were 42 vegetarians with vitamin B12 deficiency (< 156 pmol/L) selected from 118 vegetarians as members of Indonesia Vegetarian Society (IVS) Pekanbaru, treated by vitamin B12 fortified oatmeal for three months from March to June 2010. Serum vitamin B12 and homocysteine were measured by electrochemiluminescent immunoassay and microparticle enzyme immunoassay method respectively. Result: Prevalence of vitamin B12 deficiency in vegetarian was 35.6%. Statistical analysis showed a significant increase of serum vitamin B12 from 124.6 to 284.6 pmol/L (p=0.001) and significant decrease of serum homocysteine from 20.1 to 15.1 Âµmol/L (p=0.001). Conclusion: Consumption of vitamin B12 fortified oatmeal increases the level of serum vitamin B12 and decreases the level of serum homocysteine significantly in vegetarian with vitamin B12 deficiency.